2021
DOI: 10.3390/ijerph18189880
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic: A Longitudinal Study on the Emotional-Behavioral Sequelae for Children and Adolescents with Neuropsychiatric Disorders and Their Families

Abstract: This study aimed to investigate the immediate and short-term impact of the pandemic on the psychological well-being of Italian children and adolescents with psychiatric disorders and their families. Overall, 56 patients aged 6–18 (M = 13.4 years, SD = 2.77) and their parents were evaluated during the COVID-19 lockdown (T0) and after 4 months (T1). An ad hoc data sheet, Youth Self-Report 11–18 (YSR), Child Behavior Checklist 6–18 (CBCL), and Depression Anxiety Stress Scale-21 (DASS-21) were administered. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Italian studies [ 14 , 24 ] on children and adolescents with psychiatric disorders found a worsening of psychological distress in patients with externalizing behavioral symptoms, while patients with internalizing disorders showed a better adaptation to the pandemic context. Furthermore, there was a significant positive correlation between internalizing symptoms of children and parental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Italian studies [ 14 , 24 ] on children and adolescents with psychiatric disorders found a worsening of psychological distress in patients with externalizing behavioral symptoms, while patients with internalizing disorders showed a better adaptation to the pandemic context. Furthermore, there was a significant positive correlation between internalizing symptoms of children and parental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our sample was mainly composed of pediatric inpatients hospitalized before the outbreak of the pandemic (i.e., 2015–2019), and the rate of inpatients hospitalized in 2019 is almost equal to that of 2020; therefore, we did not observe an increase in admissions for suicidality from the year immediately before the pandemic to the year of the outbreak of the pandemic. This finding is probably due to the imposed restriction on territorial mental health services and scheduled hospitalizations during the COVID-19 pandemic [ 49 ], but it may also be related to the fact that for some young people the effects of the pandemic on mental health have not been immediately observed; in fact, previous studies on children and adolescents with preexisting neuropsychiatric disorders showed a general good adjustment of young patients to the pandemic situation [ 126 , 127 , 128 ]. However, the long-term negative impact of the pandemic on the psychological well-being of youth could emerge later [ 129 ], so we would expect an increase in suicidality rate in the following years.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that our group of adolescents showed a fairly good adjustment to the pandemic situation, at least in its first phase. It seems safe to reason that a decreased exposure to an in-person school environment might have led to a reduction in several peer stressors and victimization (for those who experienced it), and academic performance triggers [ 72 , 73 ], which would normally cause distress, anxiety, and depression [ 74 ]. The shift to a rather “safe” environment such as the domestic one might not have weighted as much on our sample’s psychological well-being, producing relative stability.…”
Section: Discussionmentioning
confidence: 99%